Multifactorial regression model of natural and anthropogenic urban systems interaction - Banakh А.; Poltavets М. (Ways to Improve Construction Efficiency, 2019)
In the article the generalized parameters of natural and anthropogenic urban systems are defined, their correlation analysis is made, the resulting factor is selected. On the basis of actual data of field surveys, a three-dimensional regression of generalized variables is calculated. A multifactorial regressive model of the natural and anthropogenic urban systems interaction is formed and analyzed.